Brain-derived neurotrophic factor promoter methylation and cortical thickness in recurrent major depressive disorder - Na, Kyoung-Sae; Won, Eunsoo; Kang, June; Chang, Hun Soo; Yoon, Ho-Kyoung; Tae, Woo Suk; Kim, Yong-Ku; Lee, Min-Soo; Joe, Sook-Haeng; Kim, Hyun; Ham, Byung-Joo (Scientific reports, 2016)
Recent studies have reported that methylation of the brain-derived neurotrophic factor ( BDNF ) gene promoter is associated with major depressive disorder (MDD). This study aimed to investigate the association between cortical thickness and methylation of BDNF promoters as well as serum BDNF levels in MDD. The participants consisted of 65 patients with recurrent MDD and 65 age- and gender-matched healthy controls. Methylation of BDNF promoters and cortical thickness were compared between the groups. The right medial orbitofrontal, right lingual, right lateral occipital, left lateral orbitofrontal, left pars triangularis, and left lingual cortices were thinner in patients with MDD than in healthy controls. Among the MDD group, right pericalcarine, right medical orbitofrontal, right rostral middle frontal, right postcentral, right inferior temporal, right cuneus, right precuneus, left frontal pole, left superior frontal, left superior temporal, left rostral middle frontal and left lingual cortices had inverse correlations with methylation of BDNF promoters. Higher levels of BDNF promoter methylation may be closely associated with the reduced cortical thickness among patients with MDD. Serum BDNF levels were significantly lower in MDD, and showed an inverse relationship with BDNF methylation only in healthy controls. Particularly the prefrontal and occipital cortices seem to indicate key regions in which BDNF methylation has a significant effect on structure.